The relationship between health self-perception, food consumption and nutritional status among Portuguese older adults - Babo, M. (2019)
In Portugal people aged 65 and above will be the populational group with the highest growth rate of the next decades. Healthy ageing constitutes a challenge as not only the number of years lived are essential, but also the quality of life becomes a priority. The aim of this study was to understand the relationship between health self-perception (HSP), food consumption and nutritional status among Portuguese older adults. Four hundred fifty-nine older adults (aged 65) were interviewed, almost half had a positive HSP. The most significant predictor of HSP was nutritional status, p = 0.005, but independence in shopping had the largest impact on how they compared to others, p < 0.001. Interventions need to focus on factors like nutritional status, independency on Activities of Daily Living, Satisfaction with Food-Related Life and utilize them to modify the negative HSP and attitudes towards ageing and health and maximize the positive aspects of old age. (c) 2019, Springer Nature Limited.